Genetic variability of yield and its contributing characters on CIMMYT maize inbreds under drought stress (Bangladesh Journal of Agricultural Research, 2015)
This experiment was conducted in a randomized block design with three replications at Bangladesh Agricultural Research Institute, Gazipur-1701 during the rabi season of 2010 with 25 maize inbred lines. Correlation and path coefficient analysis were done for yield and some other traits. Genotypic variations were observed for ear height and grains/row. The highest broad sense heritability (h2b) was observed for yield/plant followed by ear height and 1000- grain weight. Maximum genetic advance in percentage of mean (GA) was recorded for yield/plant (92.652) and ear height (75.87). The yield/plant showed significant positive genotypic correlation (rg) with cob diameter (0.440) and grains/row (0.265). Significant negative correlation was observed between ear height and yield and also for days to 50% tasseling. The highest direct positive effect was obtained for rows/cob. These studies suggest that cob diameter, row per cob, grains/row and ear height were the most important yield contributing factors and an attempt should, therefore, be made for an effective selection of these traits. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21985 Bangladesh J. Agril. Res. 39(3): 419-426, September 2014